2013
DOI: 10.1038/srep03541
|View full text |Cite
|
Sign up to set email alerts
|

Narrow Energy Gap between Triplet and Singlet Excited States of Sn2+ in Borate Glass

Abstract: Transparent inorganic luminescent materials have attracted considerable scientific and industrial attention recently because of their high chemical durability and formability. However, photoluminescence dynamics of ns2-type ions in oxide glasses has not been well examined, even though they can exhibit high quantum efficiency. We report on the emission property of Sn2+-doped strontium borate glasses. Photoluminescence dynamics studies show that the peak energy of the emission spectrum changes with time because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 33 publications
1
44
1
Order By: Relevance
“…The main lifetime τ 1/e of these relaxation processes is on the order of microsecond, indicating that the observed emission may be attributed to a T 1 -S 0 transition. (1,15) Although these emission decay curves are similar, the decay constants of these glasses are slightly different. Table 1 shows the decay constants of these glasses.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The main lifetime τ 1/e of these relaxation processes is on the order of microsecond, indicating that the observed emission may be attributed to a T 1 -S 0 transition. (1,15) Although these emission decay curves are similar, the decay constants of these glasses are slightly different. Table 1 shows the decay constants of these glasses.…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that the Sn 2+ emission peak shifted toward lower photon energy as time elapsed after UV irradiations. (15,16) Considering the PL spectral shape and the PL decay constant, this assumption about the local coordination state of Sn 2+ can be explained without contradiction. The shortened lifetime is considered to be correlated to the aggregation of Sn 2+ species, which is suggested in optical absorption spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a)]. 8), 15) In addition, no variation in the spectra was observed as a function of excitation photonenergy. On the other hand, in the glasses processed above 1100°C (i.e., SZB1200 to SZB1500), the shoulder/band appeared additionally at ³2.02.5 eV, which is lower than the broad (blue) PLband [Figs.…”
Section: )11)mentioning
confidence: 99%
“…SnO-containing glass has absorbed much attention because the glass possess a large quantum-yield (QY) for visible blue-PL caused by T 1 S 0 relaxation based on s 15) and consequently SnO-containing glass is regarded as a possible candidate for RE-free phosphor and scintillator material. 8), 16) In addition, glass in ZnOB 2 O 3 system, which consists of a typical strong former, is frequently studied from optical/spectroscopic point of view.…”
Section: )11)mentioning
confidence: 99%